Repeatability of exercise‐induced changes in mRNA expression and technical considerations for qPCR analysis in human skeletal muscle. Issue 3 (10th February 2019) - Islam, Hashim; Edgett, Brittany A.; Bonafiglia, Jacob T.; Shulman, Talya; Ma, Andrew; Quadrilatero, Joe; Simpson, Craig A.; Gurd, Brendon J.
Abstract : New Findings: What is the central question of this study? Are individual changes in exercise‐induced mRNA expression repeatable (i.e. representative of the true response to exercise rather than random error)? What is the main finding and its importance? Exercise‐induced changes in mRNA expression are not repeatable even under identical experimental conditions, thereby challenging the use of mRNA expression as a biomarker of adaptive potential and/or individual responsiveness to exercise. Abstract: It remains unknown if (1) the observed change in mRNA expression reflects an individual's true response to exercise or random (technical and/or biological) error, and (2) the individual responsiveness to exercise is protocol‐specific. We examined the repeatability of skeletal muscle PGC‐1α, PDK4, NRF‐1, VEGF‐A, HSP72 and p53 mRNA expression following two identical endurance exercise (END) bouts (END‐1, END‐2; 30 min of cycling at 65% of peak work rate (WRpeak ), n  = 11) and inter‐individual variability in PGC‐1α and PDK4 mRNA expression following END and sprint interval training (SIT; 8 × 20 s cycling intervals at ∼170% WRpeak, n  = 10) in active young males. The repeatability of key gene analysis steps (RNA extraction, reverse transcription, qPCR) and within‐sample fibre‐type distribution ( n  = 8) was also determined to examine potential sources of technical error in our analyses. Despite highly repeatable exercise bout characteristics (work rate, heart rate, blood lactate; ICC > 0.71; CV < 10%; r  > 0.85, P <  0.01), gene analysis steps (ICC > 0.73; CV < 24%; r  > 0.75, P <  0.01), and similar group‐level changes in mRNA expression, individual changes in PGC‐1α, PDK4, VEGF‐A and p53 mRNA expression were not repeatable (ICC < 0.22; CV > 20%; r <  0.21). Fibre‐type distribution in two portions of the same muscle biopsy was highly variable and not significantly related (ICC = 0.39; CV = 26%; r  = 0.37, P  = 0.37). Since individual changes in mRNA expression following identical exercise bouts were not repeatable, inferences regarding individual responsiveness to END or SIT were not made. Substantial random error exists in changes in mRNA expression following acute exercise, thereby challenging the use of mRNA expression for analysing individual responsiveness to exercise. Abstract :